A retrospective study comparing the efficacy of dose-dense chemotherapy, intraperitoneal chemotherapy and dose-dense chemotherapy with hyperthermic intraperitoneal chemotherapy in the treatment of advanced stage ovarian carcinoma. (January 2020) - Rettenmaier, Mark A.; Micha, John P.; Bohart, Randy; Goldstein, Bram H.
Abstract: Objectives: Hyperthermic intraperitoneal chemotherapy (HIPEC), intraperitoneal chemotherapy (IP) and dose-dense (DD) chemotherapy have been employed with varying success in the treatment of advanced stage ovarian carcinoma. Despite the clinical benefits associated with these specific forms of chemotherapy administration, they have not been comparatively analyzed, vis-à-vis their efficacy. Study design: Advanced stage ovarian cancer patients who were treated with platinum/taxane chemotherapy via a DD regimen (n = 100), IP approach (n = 81) or a DD regimen in conjunction with HIPEC (n = 64) were retrospectively evaluated. The clinical variables of interest were patient age, body mass index, surgery and pathology data, chemotherapy regimen, inclusion of maintenance therapy, and progression free/overall survival. Results: Progression free survival (PFS) was significantly more pronounced in the HIPEC (34.9 months) and IP (34.0 months) patients, compared to the DD group (27.6 months) (P = 0.005). A cox-proportional hazards regression model indicated that there was a decreased risk of disease progression accorded to the patients who were treated with IP chemo or HIPEC and DD chemotherapy (HR, 0.43; 95 % CI: 0.21–0.88; P = 0.022) and the subjects who underwent optimal cytoreductive surgery (HR, 2.42; 95 % CI: 1.22–4.80; P = 0.011). Positive BRCA status (HR, 0.434; 95 % CI: 1.59–3.44; P = 0.001) and number of chemotherapy regimens (HR, 1.36; 95 % CI: 1.159–1.61; P = 0.001) were significantly correlated with improved OS although we did not discern a survival benefit associated with any of the chemotherapy treatments (P = 0.136). Conclusion: We observed PFS advantages conferred to the ovarian cancer patients treated with HIPEC and IP chemotherapy compared to DD chemotherapy. However, an overall survival advantage related to the chemotherapy regimens was not borne out, possibly due to the retrospective nature of the study or differing time periods wherein the specific patient cohorts underwent treatment.